Poverty Reduction through Non-Cash Social Assistance - Soetji Andari (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2017)
The Ministry of Social of the Rep. of Indonesia launched a non-cash assistance program in liaise with Joint Business Groups (KUBE) and Hope Family Program (PKH) in the context of reducing poor society effort. It was a further stepand the government’s commitment to reduced poverty in Indonesia. The distribution of non-cash social assistance system is to prevent the one that is inappropriate in its quality and quantity. Some beneficiaries of Hope Family Program and a Through non-cash Welfare Rice Program (Rastra) attended to gather in a small shop / stall that was appointed as an electronic service provider stall (e-warong). This system is a way to prevent mala-practices of social assistance distribution and to ensure its effectiveness in reaching the target, the amount and the time allocation. This research used a qualitative approach as it was conducted to know the implementation of the non-cash social assistance in Kediri District and that of in Madiun District. The result of the research showed that it needed either legality in its implementation of e-warong, and some technical managerial assistance for the e-warong managers, and also it needed some support of internet network facilitiy and its infra-structures.